PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS, ITS IMPACT ON THE DEVELOPMENT OF HISTORICAL MEMORY (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article discusses in detail the pedagogical and psychological aspects taken as an influencing factor in the process of teaching historical sciences, its aspects affecting pedagogical activity. Of course, taking into account the age characteristics of students, we will analyze a number of effective methods, such as historical events through games and interesting stories. Due to the availability of all opportunities for trainees and the development of abstract thinking skills, more attention is paid to working with historical sources and documents.
Keywords: Pedagogical-psychological aspect, mnemonics, category, intellectual, Memory, Collective memory, Assimilation, oral history.